2015
DOI: 10.1111/acv.12198
|View full text |Cite
|
Sign up to set email alerts
|

Do natural areas in urban landscapes support successful reproduction by a group of conservation priority birds?

Abstract: If conservation priority birds are to persist in an increasingly anthropogenically altered world, suitable habitat must be created or preserved in potentially unsuitable landscapes. While natural areas in urban environments may provide habitat for declining groups of birds, little is known about effects of urbanization on the reproductive success of birds, such as grassland birds, that are typically thought to be associated with more rural landscapes. While typical conservation efforts have focused on conservi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…The effects of urbanization on nesting success of grassland birds have been little studied. However, our results agree with those recently described by Buxton and Benson (), who found that nests of grassland birds (mostly of Red‐winged Blackbird Agelaius phoeniceus ) in urban landscapes had lower nest predation rates than nests in more rural landscapes (but see Grandmaison & Niemi ). Rodewald et al .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The effects of urbanization on nesting success of grassland birds have been little studied. However, our results agree with those recently described by Buxton and Benson (), who found that nests of grassland birds (mostly of Red‐winged Blackbird Agelaius phoeniceus ) in urban landscapes had lower nest predation rates than nests in more rural landscapes (but see Grandmaison & Niemi ). Rodewald et al .…”
Section: Discussionsupporting
confidence: 93%
“…Mermoz and Reboreda () found that the rate of brood parasitism of Marshbirds nesting mostly in patches of thistles Cynara cardunculus growing in field margins along secondary unpaved roads was 65.4%, a value similar to that found in this study (agro‐patches: 72.2% and urban‐patches: 58.8%). Also for grassland birds, Buxton and Benson () observed that brood parasitism by Brown‐headed Cowbirds Molothrus ater was greater in rural areas than in urban areas, indicating that this pattern may be similar irrespective of grassland‐host species, and that it relates mainly to the abundance of brood parasites, as in both study areas the abundance of cowbirds decreased with urbanization in the landscape (Buxton & Benson , Pretelli ). Higher brood parasitism and productivity of parasite nestlings in agro‐patches would generate a system that promotes a negative feedback process whereby parasite populations benefit to the detriment of native hosts.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Consequently, using predator activity or abundance as a cue of habitat quality may cause birds to incorrectly devalue habitats within urban areas. While we have limited data on nest predator assemblages at our sites (Buxton and Benson ), nest predation was indeed lower in more urban areas. If birds also select habitat on the basis of conspecific or avian heterospecific presence, then lack of these cues in urban sites could also result in habitat avoidance (Valone ).…”
Section: Discussionmentioning
confidence: 87%
“…From mid‐May to early July in 2012 and 2013, we conducted bird surveys on 30 sites located on an urban‐to‐rural gradient throughout Cook, DuPage, Kane, and McHenry Counties, Illinois, and examined nest success at a subset of sites ( n = 9) as part of a larger concurrent study examining the effects of urbanization on grassland‐nesting birds (Fig. ; Buxton and Benson , ). Sites were dominated by grassland vegetation and included native warm‐season grasses and non‐native cool‐season grasses maintained by the county forest preserve districts.…”
Section: Methodsmentioning
confidence: 99%